PENGARUH VARIASI ARUS PENGELASAN GTAW TERHADAP SIFAT MEKANIK PADA MILD STEEL - Kristiana pasau; Salma Salu; ariyanto ariyanto (Unit Penelitian, dan Pengabdian Masyarakat (UPPM) Politeknik ATI Makassar, 2023)
This study aims to determine the effect of variations in welding current on the tensile strength and toughness of GTAW welds with ER70S-60 electrodes. The materials is welded with a current of 70 Ampere, 100 Ampere, and 130 Ampere by GTAW AC/DC reverse polarity welding using ER70S-60 electrode with a diameter of 2,4 mm X 1000 mm. AC/DC reverse polarity, ie the electrode wire holder is connected to the positive pole and the negative The type and base metal is connected to the negative pole. The type of seam used is V seam with and angle of 70°. This specimens were subjected to tensile test and impact tests. The highest tensile strength for the weld area occurs in the 130 Ampere specimen is 52.98 kgf/mm², this means an increase of 3.47 kgf/mm2 from the normal specimen and also by 6.10 kgf/mm2 of a 100 Ampere specimen. The toughness in the highest weld area on the 130 Ampere specimen is 4.03 Joules, the 70 Ampere and 100 Ampere currents have decreased to 70 Ampere currents, which are 2.69 joules and 0.009 joules, respectively. From the results of the study it can be conluded that variations in welding currents there is a change in the structure due to strength of the material, namely an increase in normal specimens.